The Effect of Semantic Feature Analysis (SFA) Strategy on Biological Self-Efficacy and Secondary School Students' Achievement of Biology (Journal Of Educational and Psychological Researches, 2025)
The research aims to examine the influence of the semantic feature analysis (SFA) strategy on biological self-efficacy and achievement in biology for secondary school male students. The researchers adopted the experimental approach with equivalent groups. A post-test was utilized for the biological self-efficacy scale and the biology subject achievement. The results showed that the experimental group's performance was greater than that of the control group in each of the achievement tests and the biological self-efficacy scale. Thus, the two null hypotheses in the current research were rejected. The researchers concluded that the semantic feature analysis (SFA) strategy has a significant impact on students' academic achievement and biological self-efficacy.